The impact of extra-valvular cardiac damage on mid-term clinical outcome following transcatheter aortic valve replacement in patients with severe aortic stenosis - Pellegrini, Costanza; Duesmann, Charlotte; Rheude, Tobias; Berg, Amelie; Alvarez-Covarrubias, Hector A.; Trenkwalder, Teresa; Mayr, N. Patrick; Schürmann, Friederike; Nicol, Philipp; Xhepa, Erion; Joner, Michael (Frontiers in Cardiovascular Medicine, 2022)
Aims Severe aortic valve stenosis (AS) is associated with extravalvular cardiac damage and a novel staging model was proposed to quantify the damage. This study aimed to validate this model in patients undergoing transcatheter aortic valve replacement (TAVR) and assess its prognostic impact. Methods and results Based on echocardiographic findings, the following staging was applied: isolated AS (Stage 0), left ventricular damage (stage 1), left atrial or mitral valve damage (stage 2), pulmonary hypertension or tricuspid regurgitation (stage 3), or right ventricular dysfunction (stage 4). The primary endpoint was all-cause mortality at two years. Distribution across stages was 0.8% at stage 0, 7.5% at stage 1, 63.3% at stage 2, 18.3% at stage 3 and 10.1% at stage 4. All-cause mortality increased for each stage 1 through 4 (12.1%, 18.2%, 26.6% and 28.2%; p=0.023). In the multivariate model, stage of cardiac damage, age, NYHA class III/IV, peripheral artery disease and previous pacemaker were independent predictors of the primary endpoint. Conclusions Patients treated for severe AS show high prevalence of extravalvular cardiac damage. Increase in stage is associated with higher all-cause mortality at two years. Application of this staging model may provide an additive value to current treatment algorithms.